2009
DOI: 10.4038/cmj.v54i4.1450
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antenatal risk conditions among women in an underserved district of Northern Sri Lanka

Abstract: Objective To assess the prevalence of risk conditions among antenatal women in the Vavuniya District.Design and setting A cross-sectional study was conducted among 392 pregnant women who had completed 36 weeks of gestation and were admitted or referred to two leading hospitals in the district.Measurements Women were interviewed consecutively using a questionnaire, and their antenatal details were extracted from records by trained investigators. Data on socio-demographics, antenatal care utilisation, risk condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In this study the estimates of anaemia in non pregnant women were as high as 35% in some regions [3]. Regional studies on the prevalence of anaemia in pregnant women have reported a prevalence of 14.4% in Dankotuwa in the Puttalam district in 1999, 8.2% in northern Sri Lanka in 2009 and 14.1% in the Anuradhapura district in 2012 [4][5][6]. Although demonstrating a wide variation in the rates reported, all these regional studies suggest that the national prevalence could be less than the available estimates.…”
Section: Introductionmentioning
confidence: 91%
“…In this study the estimates of anaemia in non pregnant women were as high as 35% in some regions [3]. Regional studies on the prevalence of anaemia in pregnant women have reported a prevalence of 14.4% in Dankotuwa in the Puttalam district in 1999, 8.2% in northern Sri Lanka in 2009 and 14.1% in the Anuradhapura district in 2012 [4][5][6]. Although demonstrating a wide variation in the rates reported, all these regional studies suggest that the national prevalence could be less than the available estimates.…”
Section: Introductionmentioning
confidence: 91%
“…A study done in the Puttalam district in 1999 reported a prevalence of 14.4% and another study conducted in the adjacent Gampaha district in 2001-2002 period reported 7.1% prevalence [3]. In 2009, a 8.2% prevalence was reported from the Vavuniya district [5]. The prevalence was 18-23.4% in Colombo.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to selfnegligence and suboptimal dietary care. Inadequate antenatal care in unplanned pregnancies is also phenomenal in other countries as well(20,56,57). Currently in the USA, pregnant women with unintended pregnancies were associated with cigarette smoking and lack of adequate vitamins (58).…”
mentioning
confidence: 99%